Education in citizenship: an approach to its conceptualization. Actions and strategies around the scope of social coexistence and the recognition of sociocultural diversity (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2024)
Coexisting in harmonious, civic and functional education constitutes tasks typical of citizenship education, which seek to strengthen bonds of understanding between individuals with diverse sociocultural and identity belongings, in whom it seeks to develop the conviction about equal, fair coexistence and permeated by freedom positive.This research is the result of a documentary review, initially on the conceptualization of education in citizenship and, then, the proposal of actions and strategies from which to build positive scenarios, in which social coexistence and recognition are possible of sociocultural diversity. Operating in this sense demands from educational processes a greater sense of openness and relevance around the promotion of a critical spirit, the promotion of universal values and common principles from which it is possible to achieve inclusion, respect for pluralism, the recognition of human dignity and the transcendence towards the praxis of responsible, reflective and open attitudes to the true involvement of the Other, socially, culturally and ideologically different, in an attempt to avoid destructive discrimination and hostile treatment, as risk factors capable of violating both the psychosocial integrity and the human rights that assist each individual. It is concluded that education in citizenship as a process that seeks to underpin civility, collective responsibility, tolerance and solidarity, demands synergistic efforts of the socialization factors, with the purpose of achieving a coexistence based on the unification of wills around common purposes.
Keywords: civic attitudes; citizen coexistence; sociocultural diversity; universal values; human virtues